Family Education Models Of Kiai‘S Pesantren: Transfer Of Lora/Ning’s Caracter In Pamekasan - Rijal, Akh Syaiful; Thohir, Muhammad; Aliwafa, Aliwafa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The purpose of this study was to determine the educational model of the pesantren kiai's family in shaping the character of lora/ning in Pamekasan. By using a qualitative approach in the form of descriptive-analytic research, the researchers targeted several pesantren in Pamekasan Regency which were represented by various models of pesantren, that is pesantren of salaf, pesantren of semi modern and pesantren of Modern. The results of this study are that the educational model of the pesantren kiai's family to cultivate the character of lora/ning is; First the tarbawiah model in carrying out various activities that emphasize exemplary aspects, such as: worshiping, praying, reading the Qur'an, qiyamul lail, hanging out with pious people, obligatory fasting, sunnah fasting on Mondays and Thursdays, and multiplying dhikr every time, and the two models of ta'limiah in carrying out various activities that emphasize knowledge, such as: awakening from an early age to study, growing awareness of thinking, maintaining health ratios, and social education.